Analisis Segmentasi Silabel dan Fonem dalam Kalimat Perintah (Kajian Fonologi) - Farah Nur; Dedy Eko Aryanto; Nelita Indah Islami (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2021)
This study aims to explain and analyze the segmentation of syllables and phonemes in command sentences using phonological studies. This research uses descriptive quantitative method. The data collection technique used was the analysis of data interpretation and the data source used came from an informant who then segmented the voice of the informant using the PRAAT application. The six data discussed in this study are: (1) images of the annotation results of sound segmentation using the PRAAT application, (2) the number of words, syllables, and syllable patterns in each sentence, (3) description of the number of phonemes in each sentence, (4) sentence duration , (5) the whole syllable, and (6) the whole phoneme. The results of this study indicate that a sentence can be analyzed and segmented using technology-based applications, from this analysis can be seen the duration, syllable, phonemes, and words. Segmentsai analysis is carried out in accordance with what the informant pronounces, so that the sound produced by the informant must be clear.